Johann Friedrich Herbart and His Mental State Theory: A Critical Review of Psychological Research (Prithvi Academic Journal, 2025)
The study of Johann Friedrich Herbart often overlooks a comprehensive account of his psychology. This paper focuses on the mental state theory, which is also the key to understanding the psychological thought. It comprehensively examines the mental state theory and related research materials, and explores the logical structure of this theory. The paper divides the mental state theory into several parts: the foundation of the theory and the mental state theory characteristics, the theory of the natural state of mind, the plasticity mental state theory, and the theory of abnormal states of mind. At the same time, this paper elaborates on the logical structure formed by the connections between these parts based on the exploration of each part. In short, Herbart's mental state theory is composed of various parts following a certain logical structure. Moreover, the mental state theory can provide insights into psychological studies today.